Sistem Pemantauan Kapasitas Sampah Berbasis IoT (SiKaSiT) untuk Pencegahan Banjir di Wilayah Sungai Citarum Bojongsoang Kabupaten Bandung - Mukhtar, Husneni; Perdana, Doan; Sukarno, Parman; Mulyana, Asep (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2020)
ABSTRACTThe needs of flood disaster management encourage various efforts from all scientific disciplines of science, technology, and society. This article discusses the efforts to prevent flooding due to the habit of disposing of their waste into rivers through an innovative waste management system using the approach and application of Internet-based technology (IoT). Previous research has produced a prototype of the waste level monitoring system. In this research, the prototype was developed into a practical technology, called SiKaSiT (IoT Based Trash Capacity Monitoring System). This technology aims to assist janitor in monitoring, controlling and obtaining information about trash capacity and disposal time easily through an application on the smartphone in real-time and online. The system was made using a level detection sensor integrated with NodeMCU and Wi-Fi, MQTTbroker-protocol and Android-based application. Furthermore, the system was implemented in Bojongsoang adjacent to the Citarum river, where the water often overflowed due to the high rainfall and volume of trash around it. The results of system testing in the field shown good performance with value ranges of reliability isÃ‚Â (99,785 - 99,944)% and availability is (99,786 - 99,945)%. SiKaSiT has several advantages over other similar systems. First, there is an application on the user's smartphone to monitor the capacity of trash and notification for full-bin. Second, the ability to operate on a small-bandwidth internet network because the throughput time is only around 0.59 kbps, thereby saving internet bandwidth consumption. This system has also helped overcome the problem of community trash management in Kampung Cijagra, where 60% of them gave feedback